Real-time information sharing, customer orientation, and the exploration of intra-service industry differences: Malaysia as an emerging market - Akhtar, Pervaiz (Tanjung Malim, 2021)
Real-time information sharing, customer orientation, and the exploration of intra-service industry differences: Malaysia as an emerging market by Akhtar, Pervaiz